Demonstrating the Unity of All Baptised Members: An Alternative Argument in Support of Children's Communion - Manurung, Philip (Jurnal Teologi Trinity, 2023)
For hundred of years Reformed churches in Indonesia have barred children from receiving the bread and wine of the Lord’s Supper. This prohibition rests on the age-of-discernment rule based on the interpretation of 1 Corinthians 11:28. Children are considered unable to self-examine and acknowledge God's body. Meanwhile, supporters of paedocommunion put forward their case by defending the rights that children have as members of God's covenant people. This study aims to offer an alternative argument to the debate by interpreting the key passage 1 Corinthians 11:17-34 and analyzing historical documents of the Reformed churches. The results of the study prove that Holy Communion is the best means of grace to express the unity of all members of Baptism. Thus, any decision regarding children participation in the Holy Communion will have an impact on the unity of the body of Christ.